ZINC DEFICIENCY IN PATIENTS WITH ACUTE CEREBRAL INSUFFICIENCY REQUIRING INTENSIVE CARE: RISK FACTORS AND PREDICTIVE MARKERS - Teriv, P.S.; Udovytska, N.O. (World of Medicine and Biology, 2019)
A double reporting observational clinical study was conducted with the participation of 60 patients with acute cerebral insufficiency requiring intensive care. The following indicators were recorded for all patients: sex, age, clinical characteristics of the patient, drug support and zinc content in the blood. Among the examined patients, the frequency of registration of hypozincemia was equal to 35%. It was established that in these patients the sex, age, assessments of depth of consciousness disorders and the severity of the patient’s condition, the presence of features of the syndrome of the systemic inflammatory response, gastrointestinal insufficiency, arterial perfusion pressure, need for artificial ventilation of the lungs and appointment of ataractics are risk factors for zinc deficiency occurrence, on the basis of which the model for predicting the development of zinc-deficient state was formed.